One-punch man. 30, The greatest obstacle - ONE, 1986- (Shonen Jump manga., 2025)
"In the deadly battle with the Monster Association, the heroes are all getting seriously injured, and to make matters worse, Garo appears as a monster, but Bang is there to face him down. Who'll have the upper hand in this master-pupil showdown?!"--